Pengaruh Optimasi Parameter Machining CNC Milling Berbasis CAD/CAM Terhadap Percepatan Waktu Pemesinan Dudukan Cetakan Kampas Rem - Ihwan Mukhtari Arifin; Eko Yudo; Nanda Pranandita (Jurnal Inovasi Teknologi Terapan, 2026)
This study analyzes the effect of optimizing CAD/CAM-based CNC milling parameters to reduce the machining time of a brake pad mold holder. The main issue addressed is the excessive machining duration caused by non-optimal cutting parameters, namely spindle speed, feed rate, and depth of cut. A quantitative experimental approach was employed using the Taguchi method and ANOVA, integrated with CAD/CAM simulation in Autodesk Fusion 360. A 3D model of the brake pad mold holder was developed and simulated to obtain machining time data from nine parameter combinations based on an L9 orthogonal array. The results show that depth of cut has the most significant influence on machining time (87.48%), followed by feed rate (12.49%) and spindle speed (0.03%). The optimal parameter combination was 3500 rpm spindle speed, 175 mm/min feed rate, and 0.6 mm depth of cut, achieving the shortest machining time of 16.633 seconds. This optimization improved machining efficiency by 78.12% compared to the initial condition. These findings confirm that integrating statistical optimization with CAD/CAM simulation can effectively accelerate high-precision manufacturing processes for automotive components.